Design factors affecting the dynamic performance of soil suspension in an agitated, baffled tank - Kashani, M.M.; Lai, S.H.; Ibrahim, S.; Birgani, P.M. (Maney Publishing, 2016)
The effects of particle size, impeller clearance and impeller speed are assessed to show how condition variations influence power consumption in the water-solid slurry suspension in an agitated tank. The energy efficiency of slurry height variation, impeller type and diameter, and solid movement speed has been investigated with six soil series stirred in a soil-water slurry. Coarser sand particles are observed to significantly increase power consumption, while finer particles, for instance clay, decrease the stirring power requirement. The 3-blade HR100 SUPERMIX® impeller manufactured by SATAKE generally performs more efficiently than a conventional 4-pitched blade turbine. The impeller's geometric design, including diameter and number of blades influences the impeller's energy efficiency, and HR100 impellers with greater diameters remarkably reduce power consumption. The tests demonstrated that the power required to provide off-bottom solid suspension and solid dispersion can be reduced dramatically by increasing the slurry height rather than by accelerating the impeller, if this option is possible.